Caribbean Report 13-02-1991 - Whitehorne, Pat (anchor); Crosskill, Hugh (correspondent); Pursue, Eugene (interviewee); Basdeo, Sahadeo (interviewee); Balintulo, Marcus (interviewee); Bazin, Marc Louis (interviewee); Morris, Bill (interviewee); Hart, Richard (interviewee); Gray, Annemarie (interviewer) (The British Broadcasting Corporation, 1991)
As the war in the Gulf enters its 4th week, Caribbean Diplomats believe that it is time for the General Assembly to assess the situation. However, Dr. Sahadeo Basdeo of Trinidad and Tobago maintains that CARICOM’s position to support the war was a principled one. Commonwealth Foreign Ministers will be meeting in London to review the parliamentary speech by South Africa’s President, F.W. DeKlerk who promised to abolish the remaining apartheid laws. The appointment of the new Haitian Prime Minister, René Garcia Préval should be ratified on Thursday. The Deputy Secretary General of Britain’s powerful Transport and General Workers Union is tipped to take over the Union’s leadership when the President retires next year. It is reported that Jamaican born, Jim Williams who was the first black Lord Major to be installed in Bristol last year, has been kicked out of his seat because he is not left enough.
1. Headlines (00:00-00:29)
2. As the war in the Gulf moves into its 4th week there is growing concerns by Caribbean diplomats that the war is exceeding the mandate which was given through the United Nations Resolution. These diplomats believe that it is time for the General Assembly to assess the situation. Trapped in a powerless position, CARICOM governments are being left open to condemnation by their harshest critics. Trinidad and Tobago’s Foreign Minister, Dr. Sahadeo Basdeo firmly rejects the criticisms made on Caribbean leaders and maintains that CARICOM’s decision to support the war was a principled one. Mr. Eugene Pursue, Grenada Ambassador to the United Nations indicates that there is concern regarding the United Nation’s role in the war, which includes consultation (00:30-04:57)
3. Commonwealth Foreign Ministers will be meeting in London to review the parliamentary speech made by South Africa’s President, F.W. DeKlerk in which he promised to abolish the remaining apartheid laws. The European Community has warmly welcomed this promise but the question remains whether the Commonwealth should adopt the same line. Dr. Marcus Balintulo, a Black South African Sociologist who lectures at the University of the West Indies in Trinidad and Tobago, believes that the President is moving in the right direction. However, Dr. Balintulo argues that there is still some way to go before South Africa can be allowed to return to the community of nations (04:58- 08:53)
4. The appointment of the new Haitian Prime Minister, René Garcia Préval should be ratified on Thursday. President Aristide has nominated 48 years old, Mr. Préval, a bakery owner, Human Rights activist and close ally to the President. Mr. Mark Bazin whose party placed 2nd in the elections, is waiting to see if he would be called upon for a cabinet post (08:54 -10:48)
Keywords: Gulf war.; Caribbean Community.; Basdeo, Sahadeo.; Haiti – Politics and government – 20th century.; Jamaica – Politics and government – 20th century.; Jamaica – economic aspects.; Labour unions – Jamaica.; Labour unions – United Kingdom.; United Kingdom – Politics and government.; Political parties – United Kingdom.; Préval, René.; Aristide, Jean-Bertrand.; Williams, Jim.; Trade Unions – Jamaica.; De Klerk, F. W. ǂq (Frederik Willem); Britain Transport and General Workers Union.; Grant, Cedric.; European Community.; CARICOM.